Prolapso de la válvula mitral. Estudio de 20 casos. - González Font, Antonio E.; Bolaños, Reynaldo; Marrero Martínez, Ulpita; Fránquíz Cuéllar, Pedro; Rodríguez, Omar; Arista Salado, Oscar (Revista Cubana de Pediatría, 2025)
Se estudiaron 20 pacientes con prolapso de la válvula mitral.